2011
DOI: 10.1186/1741-7015-9-64
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on SIDS pathogenesis. The hypotheses: plausibility and evidence

Abstract: Several theories of the underlying mechanisms of Sudden Infant Death Syndrome (SIDS) have been proposed. These theories have born relatively narrow beach-head research programs attracting generous research funding sustained for many years at expense to the public purse. This perspective endeavors to critically examine the evidence and bases of these theories and determine their plausibility; and questions whether or not a safe and reasoned hypothesis lies at their foundation. The Opinion sets specific criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 130 publications
0
26
0
Order By: Relevance
“…In our current study, dead pups were rapidly eaten by the dam, so the quality of tissue available for autopsy was poor. It will be important to analyse the cause of death by ECG telemetry and immediate autopsy, to compare with human pathological findings in SIDS (Goldwater, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current study, dead pups were rapidly eaten by the dam, so the quality of tissue available for autopsy was poor. It will be important to analyse the cause of death by ECG telemetry and immediate autopsy, to compare with human pathological findings in SIDS (Goldwater, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Since the ‘back to sleep’ campaign in 1994, there have been no further reductions in SIDS incidence. A number of causative mechanisms have been proposed to lead to SIDS, but without any unifying theory or correlation with pathological findings (Goldwater, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…A wide range of factors from maternal behaviors such cigarette smoking and substance abuse (Iyasu et al, 2002; Blair et al, 2006; Horne, 2006; Moon et al, 2007; Moon, 2011) to sleeping conditions such as soft bedding and sleeping in the prone position (Willinger et al, 1994; Mitchell et al, 1999b; Mitchell et al, 1999a) have been identified with an increased risk for SIDS. Although, we have gained many new insights into the mechanistic basis of this syndrome, there are still many open questions (Morris, 1999; Kinney et al, 2009; Goldwater, 2011; Tfelt-Hansen et al, 2011). This complexity in the etiology of SIDS is readily exemplified by the shifts in SIDS demographic data.…”
Section: Cardiorespiratory Dysautonomiamentioning
confidence: 99%
“…It is defined as the unexpected sudden death of a child less than 1 year of age in which an autopsy does not show an explainable cause of death (Hauck and Tanabe, 2008). Although the underlying mechanism has remained elusive; several theories propose failure of respiratory and/or cardiac pathways (Guntheroth, 1995; Horne et al, 2005; Goldwater, 2011; Garcia et al, 2013). Petechiae on autopsy of SIDS cases as well as histological evidence of mild respiratory infection in a high percentage of SIDS victims favor a respiratory-related related mechanism (Guntheroth, 1995; Trachtenberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%